Comparison of abdominal muscle patterning in the tennis serve using different footwork techniques - Zmajic, H. (Medicine and Science in Tennis, 2003)
The serve is the only stroke in which the tennis player has total control over the timing, speed, direction and rotation of the ball, without any influence from the opponent. It is also one of the most complex tennis strokes and requires long years of practice in order to perform it with confidence during a competition. Of course, with such a complex movement there are significant individual differences regarding the form and the stroke rhythm. References describe two footwork techniques - foot up and foot back.2 In view of the observed differences, it can be assumed that there are also differences in muscular activity, which is, in fact, the basis of all movement.